Paulo Freire and the educational links of knowledge: Contributions of his thought to Contemporary Brazilian Education - Carreira , Beatriz Fernanda; Silva, Kênia Mara da Costa Jacob; Barbosa, Zuleide Aparecida Julião (Seven Editora, 2023)
This text aims to conduct reflections on the contributions of Paulo Freire’s ideas to Brazilian education. For this, it approaches in a synthetic way the history of Education from Antiquity to the present day, going through several theoretical studies based on authors such as Vernant (2011), Le Goff (n.d.), Descartes (1996), Durkheim (2013), Dewey (2007), Ferreira and Bittar (2008), Boto (2007), Marcondes (2007), Santos (2003), Garcia (2007), as well as works of the author himself highlight of this work: Paul Freire. To this end, it seeks to answer the following question: what is the contribution of Paulo Freire’s ideas to contemporary Brazilian education? With this, we realize that such a thinker contributed and still contributes, through his works, significantly in the education that has as perspective the human emancipation and the search for the transformation of the social reality. Although, analyzing the neoliberal context that we live, his theory is the target of criticism, since it acts against the hegemony is a landmark at the world level and collaborated in the elaboration of new educational paradigms, which now make it possible to think about the relationship between popular knowledge and scientific knowledge. DOI:https://doi.org/10.56238/ptoketheeducati-045